Postoperative Ultrasound in Kidney Transplant Recipients: Association Between Intrarenal Resistance Index and Cardiovascular Events. Issue 8 (August 2020) - van de Kuit, Anouk; Benjamens, Stan; Sotomayor, Camilo G.; Rijkse, Elsaline; Berger, Stefan P.; Moers, Cyril; Bakker, Stephan J.L.; Minnee, Robert C.; Yakar, Derya; Pol, Robert A.
Abstract : Background: Doppler ultrasound, including intrarenal resistance index (RI) measurement, is a widely used modality to assess kidney transplantation (KTx) vascularization. The aim of this study is to gain insight in the associations between early postoperative RI measurements and cardiovascular events (CVEs), all-cause mortality, and death-censored graft survival. Methods: From 2015 to 2017, a prospective cohort study was conducted in patients in which RI measurement was performed immediately after KTx. The RI was calculated as (peak systolic velocity—end-diastolic velocity)/peak systolic velocity. End points were CVEs, all-cause mortality, and graft failure. Kaplan-Meier analyses (logrank test) were used for differences in end points. Univariate and multivariate associations were investigated by means of Cox regression analyses. Results: RI cutoff of 0.70 was used. We included 339 recipients, of which 271 (80%) had an RI ⩽ 0.70 and 68 (20%) had an RI > 0.70. CVEs were observed in 27 (8%) patients, 27 (8%) patients died, and 17 (5%) patients had graft failure during a median follow-up of 37 months (interquartile range, 33–43). Kaplan-Meier analyses and univariate Cox regression indicated a significant association with overall CVE-free survival (hazard ratios [HR], 2.79; P = 0.011; logrank test, P = 0.008) and all-cause mortality (HR, 2.59; P = 0.017; logrank test, P = 0.013) for patients with an RI above and below 0.70. An independent association was shown between an RI > 0.70 and CVE-free survival (HR, 2.48; P = 0.042) when deceased donation was not included in the model. Conclusions: In the early postoperative period, a high RI showed to be associated with CVEs after adjustment for cardiovascular risk factors, whereas no independent association was found with overall survival and graft failure. For the interpretation of RI measurements after KTx surgery, patients' cardiovascular state should be taken into consideration.